Bull ́s Eye Maculopathy in a patient treated with efavirenz - Vaz Pereira, Cristina (2015)
Objective: To report a case of retinal toxicity associated with efavirenz in an adult. Methods: We describe a case of gradual-onset blurry vision in both eyes in a 37-year-old HIV caucasian woman, on antiretroviral therapy (ART), including efavirenz. Results: The patient presented with a best corrected visual acuity of 20/100 for the right eye (RE) and 20/125 for the left eye (LE). Fundoscopy revealed mottled atrophic changes of the macular retinal pigment epi- thelium (RPE) in both eyes. Fluorescein angiography revealed an annular pattern of RPE atrophy in both eyes. Full-field electretinography (ERG) was normal. Conclusions: Based on our patient ́s history and on previous reports, efavirenz seems to be the culprit in this case. Our report provides evidence in support of routine ophthalmological evalua- tion of patients on efavirenz.